Which infancy growth parameters are associated with later adiposity? The Cambridge Baby Growth Study - Ken K. Ong; Tuck Seng Cheng; L. Olga; P. M. Prentice; C. J. Petry; I. A. Hughes; D. B. Dunger (Annals of Human Biology, 2020)
Background: Highly consistent positive associations are reported between infancy growth and later obesity risk. However, it is unclear whether infancy growth parameters beyond body weight add to the prediction of later obesity risk. Aim: To assess whether infancy length and skinfold thicknesses add to infancy weight in the prediction of childhood adiposity. Subjects and methods: This analysis included 254 children with available data on infant growth from birth to 24 months and childhood adiposity at age 6–11 years measured by DXA. Multilevel linear regression was used to examine the predictors of childhood percent body fat (%BF), with adjustment for sex and age at follow-up visit. Results: Birth weight and weight gain (modelled as changes in z-score) between 0–3 months and 3–24 months showed independent positive relationships with childhood %BF. The addition of gains in infant length and skinfolds between 0–3 months, but not 3–24 months, improved overall model prediction, from 18.7% to 20.7% of the variance in childhood %BF (likelihood ratio test, p < 0.0001), although their independent effect estimates were small (infant length gain: negative trend, partial R-square 0.6%, p = 0.2; skinfolds: positive trend, 1.3%, p = 0.09). Conclusion: Infancy length and skinfolds contribute significantly, but only modestly, to the prediction of childhood adiposity.